2018
DOI: 10.3892/mmr.2018.9339
|View full text |Cite
|
Sign up to set email alerts
|

Triticum�aestivum sprout extract attenuates 2,4‑dinitrochlorobenzene‑induced atopic dermatitis‑like skin lesions in mice and the expression of chemokines in human keratinocytes

Abstract: Atopic dermatitis (AD) is a common chronic, recurring, inflammatory skin disease. A number of researchers have been seeking safe AD therapies for a long time. Triticum aestivum sprouts (TAEE), known as wheatgrass, are one of the most widely used health foods worldwide. They show numerous beneficial effects, including anticancer, anti‑inflammatory, anti‑oxidant, anti‑obesity, anti‑colitis and anti‑allergy effects; however, their effect on AD is unknown. In the present study, the anti‑AD effects of a 70% ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The viability of HaCaT cells was evaluated using the MTT assay. The MTT assay was carried out as previously described (Lee et al, 2018). Briefly, cells were seeded into a 96-well plate at 1 × 10 4 cells/well, and treated with various concentrations of CBT (0, 12.5, 25, 50, 100 µg/ml) for 24 h in a 37°C incubator.…”
Section: Mtt Assaymentioning
confidence: 99%
“…The viability of HaCaT cells was evaluated using the MTT assay. The MTT assay was carried out as previously described (Lee et al, 2018). Briefly, cells were seeded into a 96-well plate at 1 × 10 4 cells/well, and treated with various concentrations of CBT (0, 12.5, 25, 50, 100 µg/ml) for 24 h in a 37°C incubator.…”
Section: Mtt Assaymentioning
confidence: 99%
“… 50 36 Massa Medicata Fermentata Tonification Triticum aestivum L. exerted protective effects in an experimental animal model of chronic fatigue syndrome. 51 Whitening Triticum aestivum sprout extract attenuated 2,4-dinitrochlorobenzene-induced atopic dermatitis-like skin lesions in mice and chemokine expression in human keratinocytes. 52 37 Morindae Radix Tonification Polysaccharides from the roots of Morinda officinalis exhibited anti-fatigue effects in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of wheatgrass anti-inflammatory properties was obtained from one animal study and from two small human intervention studies that demonstrated alleviation of inflammatory disease symptoms [44][45][46]. Wheatgrass has been shown to alleviate the symptoms of atopic dermatitis in a mice animal model [46]; and two intervention studies demonstrated symptom relief following consumption of wheatgrass in patients with arthritis and ulcerative colitis (inflammatory bowel disease) [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of wheatgrass anti-inflammatory properties was obtained from one animal study and from two small human intervention studies that demonstrated alleviation of inflammatory disease symptoms [44][45][46]. Wheatgrass has been shown to alleviate the symptoms of atopic dermatitis in a mice animal model [46]; and two intervention studies demonstrated symptom relief following consumption of wheatgrass in patients with arthritis and ulcerative colitis (inflammatory bowel disease) [44,45]. The findings of the current research are supported by these studies, and may also offer a mechanism for explaining the results described above: higher concentrations of anti-inflammatory cytokine IL-10 due to wheatgrass intake may explain, at least partially, the mechanism underlying alleviation of these inflammatory disease symptoms [44][45][46].…”
Section: Discussionmentioning
confidence: 99%